Pengaruh Budaya Organisasi Terhadap Kinerja Pelayanan Publik di Kantor Satuan Administrasi Manunggal Satu Atap (SAMSAT) Kabupaten Gorontalo Utara - Fatmah M Ngabito; Indri Potale (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
This study aims to analyze the effect of organizational culture on improving organizational performance in performing public services in North Gorontalo Samsat, so in this study using a quantitative approach where this research uses data in the form of numbers and statistics to evaluate or explain the relationship between variables. The results showed that there was a simultaneous influence between organizational culture variables in the form of idealistic elements (X1) and behavioral elements (X2) on service performance at the North Gorontalo District Samsat office. The influence of organizational culture in the form of idealistic elements (X I ) and behavioral elements (X2) on public services at the Samsat Office of North Gorontalo Regency is 78, I °/c, there is an influence between organizational culture in the form of idealistic elements (X 1) on performance public service (Y) in the North Gorontalo District Samsat Office of 96.6°/c, and there is no influence between organizational culture variables in the form of behavioral elements (X2) on public service performance (Y) in the North Gorontalo District Samsat Office.